Proper Implementation Of Therapeutic Communication In Nursing Care - Fitri Yani; Kristian Galu Wilantara; Saryanti Nur Putri Yuliasih; Tome Justino Ximenes; Vivi Nureliza; Aris Prio Agus Santoso (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2022)
Nurses are those who have the ability and authority to carry out nursing actions based on the knowledge they have acquired through nursing education and therapeutic communication is the ability or skill of nurses to help clients adapt to stress, overcome psychological disorders and learn how to relate to others and help patients to explain their health problems so that they can reduce the burden of feelings and thoughts and can take action to change the existing situation if the patient believes in what is needed. The method used is literature review, namely by analyzing books and journals related to the implementation of appropriate nursing care in therapeutic communication. In carrying out proper nursing care in therapeutic communication, nurses must know what the nurse's authority is in providing nursing care and also good communication to help patients so that patients can be helped so that patients feel satisfied with nursing services. Examples of therapeutic communication techniques are: acceptance, silence or silence, offering, rewarding, active listening, open communication, asking the patient to sequence events according to time, seeking clarification, making observations, confrontation.